I follow in the dust she raises - Martin, Linda, author; University of Alaska Press, publisher (Colorado State University. Libraries, 2015)
I Follow in the Dust She Raises is a collection of deeply personal poems born from a life sharply observed. Martin takes readers from the mountains of the West to the shores of Alaska, as she delves into the rippling depth of childhood experiences, tracks the moments that change a life, and settles into the fine grooves of age. Exploring the ties of family and grief, Martin's unflinching poetry ripples with moments of extraordinary beauty plucked from what seem like ordinary lives.
I. Running Through Shadows -- Visiting the Cemetery in Plains, Montana -- Mythology -- A Sumptuous Destitution -- Believers -- Running through Shadows -- Dancing with Mama -- A Visit from Aunt Rosie -- Logger Song -- Widowmaker -- A Young Child -- Pearly Everlasting -- II. History Lesson -- Watching Mama's Figure -- Older Sister -- Uppity -- Refusing a Man -- Moonwalking, 1969 -- Losing a Man -- City Girl -- History Lesson -- Pigeons in Montpelier -- Anonymous -- Mama Calls Herself Weary -- Mama's Will -- The Vanished -- III. After Years -- At Home Now in Homer -- After Years of Searching -- Artifacts -- Once Upon a Time -- Building a Boat -- Boy, Still Visible -- Without Fame -- Shopping for Satisfaction -- True Minds -- Marriage Vow -- Migrations -- Proof of Joy -- IV. Contemplating Autumn -- Anniversary -- Premonition -- The System -- September Clouds -- Ordinary Dangers -- Acting My Age -- Slow Day at the Glass Shop -- Harboring a Mean Streak -- Moose Seasons -- Snowed In -- Tourist -- When I Brought You Home to Mama -- Coupled -- Contemplating Autumn.
Keywords: Poetry